The effects of pre-conditioning on exercise-induced muscle damage: a systematic review and meta-analysis - Boyd, L.; Deakin, G. B.; Devantier-Thomas, B.; Singh, U.; Doma, K. (Sports Medicine, 2023)
Background: Several studies have utilised isometric, eccentric and downhill walking pre-conditioning as a strategy for alleviating the signs and symptoms of exercise-induced muscle damage (EIMD) following a bout of damaging physical activity. Objectives: This systematic review and meta-analysis examined the effects of pre-conditioning strategies on indices of muscle damage and physical performance measures following a second bout of strenuous physical activity. Data Sources: PubMed, CINAHL and Scopus. Eligibility Criteria: Studies meeting the PICO (population, intervention/exposure, comparison, and outcome) criteria were included in this review: (1) general population or "untrained" participants with no contraindications affecting physical performance; (2) studies with a parallel design to examine the prevention and severity of muscle-damaging contractions; (3) outcome measures were compared using baseline and post-intervention measures; and (4) outcome measures included any markers of indirect muscle damage and muscular contractility measures. Participants: Individuals with no resistance training experiences in the previous 6 or more months. Interventions: A single bout of pre-conditioning exercises consisting of eccentric or isometric contractions performed a minimum of 24 h prior to a bout of damaging physical activity were compared to control interventions that did not perform pre-conditioning prior to damaging physical activity. Study Appraisal: Kmet appraisal system. Synthesis Methods: Quantitative analysis was conducted using forest plots to examine standardised mean differences (SMD, i.e. effect size), test statistics for statistical significance (i.e. Z-values) and between-study heterogeneity by inspecting I2. Results: Following abstract and full-text screening, 23 articles were included in this paper. Based on the meta-analysis, the pre-conditioning group exhibited lower levels of creatine kinase at 24 h (SMD = - 1.64; Z = 8.39; p = 0.00001), 48 h (SMD = - 2.65; Z = 7.78; p = 0.00001), 72 h (SMD = - 2.39; Z = 5.71; p = 0.00001) and 96 h post-exercise (SMD = - 3.52; Z = 7.39; p = 0.00001) than the control group. Delayed-onset muscle soreness was also lower for the pre-conditioning group at 24 h (SMD = - 1.89; Z = 6.17; p = 0.00001), 48 h (SMD = - 2.50; Z = 7.99; p = 0.00001), 72 h (SMD = - 2.73; Z = 7.86; p = 0.00001) and 96 h post-exercise (SMD = - 3.30; Z = 8.47; p = 0.00001). Maximal voluntary contraction force was maintained and returned to normal sooner in the pre-conditioning group than in the control group, 24 h (SMD = 1.46; Z = 5.49; p = 0.00001), 48 h (SMD = 1.59; Z = 6.04; p = 0.00001), 72 h (SMD = 2.02; Z = 6.09; p = 0.00001) and 96 h post-exercise (SMD = 2.16; Z = 5.69; p = 0.00001). Range of motion was better maintained by the pre-conditioning group compared with the control group at 24 h (SMD = 1.48; Z = 4.30; p = 0.00001), 48 h (SMD = 2.20; Z = 5.64; p = 0.00001), 72 h (SMD = 2.66; Z = 5.42; p = 0.00001) and 96 h post-exercise (SMD = 2.5; Z = 5.46; p = 0.00001). Based on qualitative analyses, pre-conditioning activities were more effective when performed at 2-4 days before the muscle-damaging protocol compared with immediately prior to the muscle-damaging protocol, or 1-3 weeks prior to the muscle-damaging protocol. Furthermore, pre-conditioning activities performed using eccentric contractions over isometric contractions, with higher volumes, greater intensity and more lengthened muscle contractions provided greater protection from EIMD. Limitations: Several outcome measures showed high inter-study heterogeneity. The inability to account for differences in durations between pre-conditioning and the second bout of damaging physical activity was also limiting. Conclusions: Pre-conditioning significantly reduced the severity of creatine kinase release, delayed-onset muscle soreness, loss of maximal voluntary contraction force and the range of motion decrease. Pre-conditioning may prevent severe EIMD and accelerate recovery of muscle force generation capacity.